The use of Visual Auditory Simulation Technique (VASTECH) - Loh, S.C.; Ow, S.H.; Ishak, Z.; Chew, F.P. (2008)
Learning requires all learners to pay attention to what they are learning. It is therefore particularly important for learners to be on-task whenever learning tasks are performed (Ormrod, 2005). Young children with inattention problems will find difficulty in concentrating on a task, do not finish what they start, do not listen and always lose things (Lerner, 2003).Children with special needs, are especially prone to lack of attention span and thus are found to be off-task at most time during the process of learning. The objective of this research are: 1) To develop a courseware using visual audio simulation technique that incorporates multimedia flash to systematically foster the attention for normal (3-6 years chronological) and special children (7-12 years chronological); and 2) To ascertain the effectiveness of Visual Audio Simulation Technique in promoting on-task behaviour of normal (3-6 years chronological)and special children (7-12 years chronological). This research adopts both the quantitative and qualitative approaches by using a visual audio simulation technique in promoting the on-task behaviour of 50 normal and special children. The frequency of on-task behaviour before and after the intervention will be recorded. The findings of this research have yet to be obtained.